Right atrial mass in the context of recurrent non-Hodgkin’s lymphoma: atrial myxoma presenting with atrial flutter - Yavari, Arash (BMJ Publishing Group, 2009)
A case is described of a 57-year-old man with a background of low-grade bronchus-associated lymphoid tissue (BALT) non-Hodgkin’s lymphoma presenting with dyspnoea and palpitations. Diagnostic work-up revealed paroxysmal atrial flutter and the presence of a mass in the right lower lobe at bronchoscopy, with histology confirming recurrent BALTOMA. Transthoracic echocardiography (TTE) revealed a mass in the right atrium. Transoesophageal echocardiography (TOE) confirmed the presence of a fleshy, mobile pedunculated right atrial mass adherent to the interatrial septum, with features more in keeping with an atrial myxoma rather than intracardiac lymphoma. He proceeded to cardiotomy and excision of the mass with histology confirming an atrial myxoma. The clinical and echocardiographic features of atrial myxomas and intracardiac lymphomas are briefly discussed.